Canine pemphigus folliaceus: report of five clinical case - LIAPI (Μ.Β. ΛΙΑΠΗ) M. V.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ) A. F.; LEKKAS (Σ. ΛΕΚΚΑΣ) S. (Journal of the Hellenic Veterinary Medical Society, 2018)
Pemphigus folliaceus (PF), which is considered the most common autoimmune skin disease in the dog, is associated with the formation of autoantibodies directed against the desmosomes of the upper third of the epidermis, that result in loss of keratinocyte adhesion (acantholysis) and subsequent epidermal cleft formation. The clinical and histopathological findings, along with the response to treatment in 5 PF cases, either idiopathic (3/5) or secondary to trimethoprim-sulfonamides (1/5) and to allergic dermatitis (1/5), are presented and discussed, accordingly. All the 5 dogs exhibited hypotrichosis-alopecia (4/5), erythema (4/5), vesicles (1/5), pustules (5/5), crusts (5/5), epidermal collarettes (3/5), excoriations (1/5), erosions (3/5), ulcers (1/5), fissures (1/5), lichenification, thickening and folding of the skin (1/5), and footpad hyperkeratosis (1/5), that were pruritic in 3 of them. These lesions were located on the head (4/5), pinnae (4/5), limbs (3/5), body trunk (3/5) and the footpads (2/5). Diagnosis was based on the results of lesionai histopathology where the most striking finding was the presence of subcorneal pustules filled with normally looking neutrophils and acanthocytes. Moreover, pustule or crust cytology that was carried out in 3 cases, revealed clusters of acantholytic cells in 2 dogs. The treatment, that was instituted in 2/5 dogs and resulted in a complete resolution of skin lesions, was based on prednisolone in immunosuppressive dosage along with azathioprine (PF secondary to allergic dermatitis), or on a combination of dapsone, Oxytetracycline and vitamin E (idiopathic PF). The remaining 3 cases were left untreated, because one showed a spontaneous remission following withdrawal of the offending medication and the other 2 were lost to follow-up.